Hubungan Kompetensi Pedadodik Guru dengan Motivasi Belajar Siswa di MTs. Mamba’ul Ma’arif Denanyar Jombang - Adibah Adibah; Siti Iin Lutfiyah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to determine the relationship between Teacher's Pedagogical Competence and Student's Learning Motivation in MTs. Mamba'ul Ma’arif Denanyar Jombang. This type of research is quantitative, the data collection is done by observation, interviews, questionnaire and documentary distribution. While analyzing data is done by using Product Moment to find out is there any relationship between Teacher's Pedagogic Competence and Student's Learning Motivation in MTs. Mamba'ul Ma’arif Denanyar Jombang. The results showed that the Pedagogic Competencies of the Teachers possessed on average had good Pedagogic Competencies, for there were various students with low, medium and high learning motivation and there was a significant correlation with the correlation coefficient of 0.444 between the Teacher's Pedagogic Competence and Student's Learning Motivation in MTs. Mamba'ul Ma’arif Denanyar Jombang.